Implementing Inclusive Education in Early Childhood: The Roles of Social Support and Routines - Diana Diana; Fonny Dameaty Hutagalung; Edi Waluyo; Reni Pawestuti Ambari Sumanto; Akaat Hasjiandito; Fathin Farah Fadhilah (Jurnal Pemberdayaan Masyarakat, 2025)
All children are entitled to equal access to education at every level. Inclusive education aims to provide equal opportunities for all students to receive high-quality educational services. This study seeks to explore the implementation of inclusive education using the Circle Inclusive Classroom Scale (CICS) in Central Java. This research employs a quantitative approach, utilizing a survey with a total of 209 respondents in this study, consisting of 130 teachers and 79 school principals. Data collection was conducted through a Google Form utilizing an instrument adapted for the two components of the CICS. The data obtained through the CICS scale were analyzed using Microsoft Office Excel to determine scores and percentages of practices. Findings show that, in terms of the Social Environment aspect, most teachers have fostered a work environment characterized by empathetic, non-judgmental, and respectful attitudes, received various forms of support and facilities, built positive relationships, and obtained access to information. In the aspect of Structure and Routines, teachers acknowledged that experiences, standards, boundaries, and routines applied to children influence their learning process. This study contributes globally by providing empirical evidence on inclusive practice in ECE in a developing country context, thereby enriching cross-cultural perspectives and advancing the global discourse on inclusive education.